2021
DOI: 10.1108/cms-02-2020-0050
|View full text |Cite
|
Sign up to set email alerts
|

Theory of self-cultivation based on Confucianism: a supplement to social exchange theory

Abstract: Purpose Although domestic research on Chinese management is emerging, a suitable domestic theory is still needed to support and explain Chinese management practice. Given that, this paper aims to extract ideas of cultivation from Confucianism and propose a theoretical framework of self-cultivation with a purpose to provide new explanations for domestic (nondomestic as well) management practice. Design/methodology/approach Drawing from pre-Qin cultivation discourse and management practice, this paper develops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…In a collectivist culture, individuals tend to identify themselves as organizational members, paying attention to their relationships with others in the same organization. When individual interests clash with organizational interests, individuals willingly make concessions for the collective good [ 78 ]. Organizational attachment theory emphasizes that individuals’ different attachment styles affect how they approach work and their willingness and ability to exert effort [ 79 , 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a collectivist culture, individuals tend to identify themselves as organizational members, paying attention to their relationships with others in the same organization. When individual interests clash with organizational interests, individuals willingly make concessions for the collective good [ 78 ]. Organizational attachment theory emphasizes that individuals’ different attachment styles affect how they approach work and their willingness and ability to exert effort [ 79 , 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, perceived organizational support, a typical variable related to social exchange theory, may mediate the relationship between perceived CSR and job performance. In addition, social exchange theory has been widely adopted to examine attitudes in relational societies such as China (Shore et al, 2009;Duan et al, 2022). Collectivism is one of China's most widely researched cultural characteristics (Zhu et al, 2022;Zhang et al, 2022), which can also be used to distinguish between individuals in the same cultural context.…”
Section: Social Exchange Theorymentioning
confidence: 99%
“…In addition, social exchange theory has been widely adopted to examine attitudes in relational societies such as China (Shore et al. , 2009; Duan et al. , 2022).…”
Section: Theory and Hypothesismentioning
confidence: 99%
“…This centering of the cultivation of character being fundamental to leadership is one of the five main features of Confucian leadership, as identified by Chinese philosopher Lai Chen (Chen, 2015). Moreover, in a comparison of management theories between Chinese and Western cultures, Duan et al (2018) argued that the core difference exhibited by Chinese organizational culture is the thought of self-cultivation, and the starting point for Chinese leaders who seek to achieve success is to develop a Junzi personality. A qualitative study showed that this Confucian perspective has effects that can be seen in contemporary management practice in China (Su et al, 2020).…”
Section: Confucian Theory Of the Personalityleadership Relationmentioning
confidence: 99%